“Diseño de un simulador en entorno virtual Labview con el análisis de variables eléctricas y técnicas de arranque de motores trifásicos”. - Andrango Quishpe, Darwin Gilson (2021)
Within the industry today, the analysis of the electrical variables that are presented for the correct operation and starting of three-phase motors occupies an important place within the training of an electromechanical engineer. Knowing which are the favorable measures for each of the variables that can occur in the starting process of a three-phase motor, as well as their correct handling, will help the useful life of a three-phase motor to be extended. On the other hand, controlling these electrical variables physically when starting the engine is practically impossible, which makes it difficult to learn these variables. For this reason, this research work proposes the design of a starting simulator for three-phase motors through the Labview environment, a program in which all the electrical variables that affect this start are monitored and analyzed. The Labview environment is used due to the ease that the program presents for the creation of graphic virtual environments.